(3cJGH GdHjGf aj cTa CSQGQ GdWH ddYjGfs - (3eMeO Hf CMeO Hf Ydj GdMehjs
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG HOGjI hGdCNQ HdG fgGjI hHYO adeG QCjJ eG GTJed Ydjg QCjJ Cf CMRe HGHg GdYGdi cJGH CLeY ajg ef gPG Gdaf s
(3BNQgG (B:s
(3hjWHN MJi JgJQGA hjUai YfgG GdeGA hjLYd Ydjg ef Ogf GdNQhY SHYI CQWGd hjWHN HfGQ djfI MJi jPgH GdeGA hjHbi GJdOgf JeJ GdebGdI GdNGeSI hHJeGegG Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdWHs